Resenha do livro: Carbone, Mauro & Lingua, Graziano (2023). Toward an anthropology of screens: showing and hiding, exposing and protecting. Switzerland: Palgrave Macmillan. (Phenomenology, Humanities and Sciences, 2025)
Não há.
Keywords: Mauro Carbone; Graziano Lingua; Screens